Structural, Magnetic and Thermoelectric Properties of hp‐Mn3Ge5. Issue 4 (27th February 2020) - Castillo, Rodrigo; Schnelle, Walter; Bobnar, Matej; Cardoso‐Gil, Raul; Schwarz, Ulrich; Grin, Yuri
Abstract : Mn3 Ge5 was obtained by high‐pressure, high temperature synthesis. The compound adopts a Nowotny‐Chimney‐Ladder type crystal structure [tetragonal, space group P 4 n 2, a = 5.7449(1) Å, c = 13.9096(4) Å, Z = 4]. Magnetic measurements reveal a ferromagnetic transition around 40 K and metallic conductivity in the temperature range from 3 K to 350 K. Despite a low thermal conductivity, the metallic character of the sample and the low Seebeck coefficient result in low values for the thermoelectric Figure of merit, ZT . Band‐structure calculations show that the Fermi level is located slightly below a pseudo‐gap in the electronic density of states. Chemical bonding analysis in position space discloses moderate charge transfer and two‐ as well as three‐atomic directed, heteroatomic bonding involving both the manganese and the germanium atoms. Abstract :